2014
DOI: 10.4055/cios.2014.6.3.318
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Predictive Factors to be Related with the Degree of Lumbar Back Muscle Degeneration: Difference by Gender

Abstract: BackgroundThe prediction of lumbar back muscle degeneration is important because chronic low back pain and spino-pelvic imbalance have been known to be related to it. However, gender difference should be considered because there are different quality and volume of muscles between genders. The purpose of this study was to search for clinical and radiological factors to predict the degree of lumbar back muscle degeneration according to gender difference.MethodsWe reviewed 112 patients (44 men and 68 women) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…In part, the limited improvement of functional mobility in the LLIF group could be explained by the fact that individuals who present with a long duration of considerable sagittal imbalance often also have atrophy of the spinal extensor muscles, 39 40 which plays a major role in the posturing and balancing activities in older adults. 28 Although correction of LL and other sagittal parameters were achieved after LLIF procedures, the function and action of back muscles remained weakened and even worsened by surgical trauma and the presence of spinal implants.…”
Section: Discussionmentioning
confidence: 99%
“…In part, the limited improvement of functional mobility in the LLIF group could be explained by the fact that individuals who present with a long duration of considerable sagittal imbalance often also have atrophy of the spinal extensor muscles, 39 40 which plays a major role in the posturing and balancing activities in older adults. 28 Although correction of LL and other sagittal parameters were achieved after LLIF procedures, the function and action of back muscles remained weakened and even worsened by surgical trauma and the presence of spinal implants.…”
Section: Discussionmentioning
confidence: 99%
“…Several spinopelvic parameters have been described and used in the recent literature, being used to classify and categorize the spinal alignment in the sagittal plane [ 11 , 12 ]. Spinopelvic parameters may be associated with degenerative disc disease, hip and facet joint osteoarthritis [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on the association between fat infiltration of LMM and low back pain, and most of concluded that LMM fat infiltration is associated with low back pain [18,[28][29][30][31]. The prevalence and severity of LMM fat infiltration increase with age [32,33]. However, few studies have been performed to examine the association between LMM fat infiltration and SSI development following spine surgery.…”
Section: Discussionmentioning
confidence: 99%